2011
DOI: 10.4236/psych.2011.29146
|View full text |Cite
|
Sign up to set email alerts
|

How Dialysis Patients Live: A Study on Their Depression and Associated Factors in Southern Italy

Abstract: Depression is an independent risk factor of poor outcomes for Chronic Kidney Disease (CKD) patients. Perceived social support and alexithymia are psychosocial variables identified by previous studies as predictive of depression in normal controls and CKD patients. Repetitively thinking and socially sharing emotional experiences have been investigated in association with depression in normal populations. Our cross-sectional study aimed to assess the effects of perceived social support, alexithymia, mental rumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…The prognosis of depression, as we said, is considerably higher in patients with CKD than in general population [28]. The remarkable finding of a survey is that patients undergoing dialysis for more than four years indicate lower scores on scales of depression than patients in the first four years of dialysis [28].…”
Section: Depression In Patients With Ckd and Bereavementmentioning
confidence: 77%
“…The prognosis of depression, as we said, is considerably higher in patients with CKD than in general population [28]. The remarkable finding of a survey is that patients undergoing dialysis for more than four years indicate lower scores on scales of depression than patients in the first four years of dialysis [28].…”
Section: Depression In Patients With Ckd and Bereavementmentioning
confidence: 77%
“…The biomarkers of urea, creatinine, hemoglobin, hematocrit, albumin, sodium, potassium, calcium, phosphorus, and C-reactive protein (CRP) values of the subjects who participate in the study were evaluated. The median number of medications used by the patients on a daily basis was three (min-max: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Normally deviating values were determined and the relationship between the HSS, HSS subscales, TAS-20, and TAS-20 subscale scores was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Pop-Jordanova and Polenakovic reported that half of the patients who received hemodialysis treatment in Macedonia (n = 230) appeared alexithymic. 12 In a study they conducted, Sinatra et al (2011) found that the primary psychiatric outlook that accompanied depression was alexithymia in patients under hemodialysis treatment for 4 years and above. 19 As a result of our research, we found that the increase in the length of hemodialysis treatment is in direct proportion to the emergence of alexithymic symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSS has been identified in HD patients as physical (HSS-1) and psychosocial stressors (HSS-2) and the markers of physical stressors were indicated with six (2,3,7,10,11,20) questions. Questionnaires for psychosocial stressors were determined with 23 (1,4,5,6,8,9,12,13,14,15,16,17,18,19,21,22,23,24,25,26,27,28,29) items [14]. The physical hemodialysis stressor score is 6-30 and the psychosocial hemodialysis stressor score is 23-115 points.…”
Section: Hemodialysis Stressor Scale (Hss): the Scale Was Developed Bmentioning
confidence: 99%